The physical characteristics of composite bone scaffold fabricated from OPEFB-CMC, Chitosan and HA - M. Yusup, Eliza; Mahzan, Shahruddin (IJMERR, 2018)
Oil Palm is the largest agriculture in Malaysia and amongst the world. Unfortunately, difficulty occurs in which oil palm disposals lead to unpleasant contamination and bad scenery. However the combination of oil palm empty fruit bunch – carboxymethyl cellulose (CMC), Chitosan (CS) and hydroxylapatite (HA), turns the composite into biodegradable bone graft as known as porous composite. It was produced with lots of pores through co-solution and lyophilization method. Pores process is important for tissue engineering development but a little bit crucial to achieve ideal properties. An ideal bone scaffold should contain more pores for better cell proliferation and as nutrient carrier. Unfortunately, too many pores may lead to the weaknesses of the scaffold. The research had examined samples through compression tests for strength. It turns out that OPEFB-CMC, a derivation material from EFB, together with HA and CS had an increment in their toughness compared to previous research using only HA and CS. This paper intentionally presents detailed evaluation about bone scaffold fabricated from waste product as the polymer, with HA and CS for better biodegradable bone implant.